The relevance of complement in pemphigoid diseases: A critical appraisal - Papara, Cristian; Karsten, Christian M.; Ujiie, Hideyuki; Schmidt, Enno; Schmidt-Jiménez, Leon F.; Baican, Adrian; Freire, Patricia C.; Izumi, Kentaro; Bieber, Katja; Peipp, Matthias; Verschoor, Admar; Ludwig, Ralf J.; et al. (Frontiers in Immunology, 2022)
Pemphigoid diseases are autoimmune chronic inflammatory skin diseases, which are characterized by blistering of the skin and/or mucous membranes, and circulating and tissue-bound autoantibodies. The well-established pathomechanisms comprise autoantibodies targeting various structural proteins located at the dermal-epidermal junction, leading to complement factor binding and activation. Several effector cells are thus attracted and activated, which in turn inflict characteristic tissue damage and subepidermal blistering. Moreover, the detection of linear complement deposits in the skin is a diagnostic hallmark of all pemphigoid diseases. However, recent studies showed that blistering might also occur independently of complement. This review reassesses the importance of complement in pemphigoid diseases based on current research by contrasting and contextualizing data from in vitro, murine and human studies.